How Shekhinah Became the God(dess) of Jewish Feminism. (September 2014) - Devine, Luke
Shekhinah, the 'cloud of Yahweh' in the Bible, a synonym for God's presence in the rabbinic tradition, and a feminine hypostasis in the Kabbalah, is a popular theological image in contemporary Jewish feminist circles. Shekhinah currently exists in many forms: she is another name for God, feminine, relational, experiential; she is a Goddess and the singular image that is sufficiently adaptable for a diverse range of postmodern feminist interpreters. However, the processes by which Shekhinah became the God/dess of Jewish feminism have not been researched. Therefore, this article tracks the evolution of Shekhinah iconography in the Jewish tradition to gain an understanding of the appeal of these images within the context of Jewish feminism's quest for an alternative to the androcentric Holy One, blessed be He. The article then traces the extent of Shekhinah theologies engendered by Second, Third-Wave and recent Jewish feminisms concluding that the plurality of contemporary spirituality and the general rejection of 'systematic' models of theology are not necessarily problematic. Rather, Shekhinah is argued to be a binding agent for diverse religionists, and one which has become normative to Jewish feminist theology.